Risk factors analysis for acute kidney injury in the newborn infants: predictive strategies (Iranian Journal of Kidney Diseases, 2019)
Introduction. Acute kidney injury (AKI) in the newborn infants is associated with increased mortality and morbidity. The purpose of this study was to investigate the prevalence, risk factors and outcome of AKI in the premature neonates. Methods. Between January 2014 and January 2015, 206 premature neonates between 27 and 36 weeks gestations were studied in the newborn intensive care unit of Amir-AL Momenin Hospital, in Semnan, Iran. All neonates were followed-up for seven days after birth. The diagnosis of AKI was based on urine output (UOP) < 1.5 mL/kg/h for 24 hours and serum creatinine SCr > 0.3 mg/dL or increased by 150% to 200% from baseline value. Data collected included gestational age, gender, birth weight, first, and fifthminutes Apgar scores, use of mechanical ventilation, continuous positive airway pressure (CPAP), sepsis, congenital heart disease, and respiratory distress syndrome (RDS). Results. Gestational age (OR = 12.09, 95% CI = 3.51-41.63; P < .001), the use of mechanical ventilation (OR = 6.72, 95% CI = 1.44-31.41; P < .05), and the first and fifth minutes Apgar scores (OR = 0.65, 95% CI = 0.44-0.95; P < .05) were significantly related with AKI occurrence. Presence of congenital heart disease, sepsis, birth weight and RDS also had a significant relationship with AKI development (P < .05). Conclusion. The most important risk factors associated with AKI development were prematurity and low-birth weight, low 1 and 5 minutes Apgar scores, and the need for mechanical ventilation, as well as the coexistent of sepsis.